O perfil da sexualidade em homens com lesão medular - Torrecilha, Larissa Amaral; Costa, Bianca Teixeira; Lima, Fellipe Bandeira; Santos, Suhaila Mahmoud Smaili; Souza, Roger Burgo De (Pontifícia Universidade Católica do Paraná, 2014)
IntroductionAmong the consequences of spinal cord injury (SCI), there is the deficit in sexual function, which interferes in the quality of life of the individual. ObjectiveTo know and to describe the profile of the sexuality of men with SCI, comparing before and after injury periods. Materials and methodCross-sectional study with 36 men with SCI. Data were collected through a questionnaire (QSH-LM) and a screenplay. Quantitative variables were presented as mean and standard deviation. Categorical variables were presented by absolute and relative frequencies and associations were performed using the chi-square. All tests presented 5% significance. ResultThere was prevalence of paraplegic patients and complete lesions. The sexual practice, often, desire and satisfaction declined after SCI, as well as sexual responses, among these are erection, ejaculation and orgasm which declined materially after SCI. The most reported feeling during sex was the increasing cardiorespiratory response, before or after SCI, and more individuals began not to feel any sensation during sexual activity after SCI. There was a significant association between type of injury and the presence of orgasm and between sexual satisfaction and sexual practice after SCI. ConclusionIt was observed that sexual response after SCI changes in ascending order: erection, orgasm and ejaculation. It is noticed that the rehabilitation is often focused on motor skills and sexuality is rarely discussed.

Introdução Entre as consequências da lesão medular (LM), está o deficit na função sexual, o que interfere na qualidade de vida do indivíduo. Objetivos Conhecer e descrever o perfil da sexualidade de homens com LM, comparando os períodos pré e pós-lesão. Materiais e métodos Estudo transversal com 36 homens com LM. Os dados foram coletados através de um questionário (QSH-LM) e um roteiro. As variáveis quantitativas foram apresentadas por média e desvio padrão. As variáveis categóricas foram apresentadas por frequências absolutas e relativas e as associações foram realizadas através do teste Qui-quadrado. Todos os testes apresentaram significância de 5%. Resultados Houve prevalência de pacientes paraplégicos e de lesões do tipo completa. A prática, frequência, desejo e satisfação sexual decaíram após a LM, assim como as respostas sexuais. Dentre essas estão ereção, ejaculação e orgasmo, que decaíram de forma relevante após a LM. A sensação mais relatada durante o ato sexual foi o aumento da resposta cardiorrespiratória, antes ou após a LM, e mais indivíduos passaram a sentir nenhuma sensação durante a atividade sexual após a LM. Houve significativa associação entre tipo de lesão e presença de orgasmo e entre prática e satisfação sexual após a LM. Conclusão Foi observado que a resposta sexual após a LM altera na ordem crescente: ereção, orgasmo e ejaculação. Percebe-se que muitas vezes a reabilitação é focada nas capacidades motoras e a sexualidade é pouco abordada.
Profile of sexuality in men with spinal cord injury
Keywords: Traumatismos da medula espinal; Sexualidade; Fisioterapia; Spinal cord injuries; Sexuality; Physical therapy